2018
DOI: 10.1177/1470320317754178
|View full text |Cite
|
Sign up to set email alerts
|

A randomized intervention study to evaluate the effect of calcitriol therapy on the renin-angiotensin system in diabetes

Abstract: Background:Prior studies suggest that vitamin D therapy may decrease cardiovascular disease risk in type 2 diabetes (T2DM) by lowering renin-angiotensin system (RAS) activity. However, randomized human intervention studies to evaluate the effect of vitamin D receptor (VDR) agonists on RAS activity are lacking.Objective:The objective of this article is to investigate the effect of direct VDR activation with calcitriol on circulating RAS activity and vascular hemodynamics in T2DM.Methods:A randomized, double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
(61 reference statements)
0
11
0
1
Order By: Relevance
“…The eight selected full-text original articles comprise three randomized controlled trials (22)(23)(24), a short-duration prospective study (25), and four cross-sectional studies (26)(27)(28)(29). The countries where these studies were conducted are located in North America (23,24), South America (25,26), Asia (27)(28)(29), and Europe (22). All the studies were hospitalbased.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eight selected full-text original articles comprise three randomized controlled trials (22)(23)(24), a short-duration prospective study (25), and four cross-sectional studies (26)(27)(28)(29). The countries where these studies were conducted are located in North America (23,24), South America (25,26), Asia (27)(28)(29), and Europe (22). All the studies were hospitalbased.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study reported a median age of 64 years (age range: 53-71years) in the intervention group and 61 years (age range: 51-71 years) in the placebo group (23). Additionally, their gender distribution shows that both sexes were equally distributed in one study (25), with female predominance in one study (26), and male predominance in the majority of the studies (22)(23)(24)(27)(28)(29). Using the Newcastle-Ottawa Scale, the methodological quality of four cross-sectional studies reveals a star-rating of < 7 (low quality) for one study (29), and ≥ 7 (high quality) for the rest of the studies (26)(27)(28).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Vitamin D is an integral part of biology and physiology of human systems and to facilitate its beneficial, modulatory effects [17]. These include enzymatic reactions, mitochondrial function, subduing inflammation and oxidative stress, immune protection, secretion of hormones, such as insulin and PTH, and modulating the renin-angiotensin-aldosterone and FGF23-Klotho hormone systems [42]. In addition, metabolomics and transcriptomics advances will enable generation of improved longer-term extra-skeletal outcomes with targeted vitamin D therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Após três semanas de intervenção, os níveis de 1,25 (OH)2D aumentou significativamente em pacientes que fizeram uso da suplementação de calcitriol, porém nada ocorreu naqueles que fizeram uso de placebo. Não houve diminuição do mecanismo renina-angiotensinaaldosterona, entretanto ocorreu um aumento na expressão de receptores de vitamina D (Zaheer et al, 2018).…”
Section: Discussionunclassified